Students Engagement in Science during Covid-19 Pandemic: Role of Self-Efficacy Beliefs and Achievement Goals - Uluhan Kurt; Yasemin Taş (Universitas Pendidikan Indonesia, 2023)
This study investigated the relationships among achievement goals, self-efficacy beliefs, and engagement in science during COVID-19. Distance education was launched due to COVID-19, and there is a need to examine these relations in the online science learning context. Participants were 448 students between 5th and 8th graders receiving distance education for eight months. Path analysis indicated mastery-approach goals and particular self-efficacy aspects positively predicted student engagement. Science communication and conceptual understanding have become prominent among self-efficacy aspects, while higher-order cognitive skills were unrelated to student engagement. Also, negative linkages were identified between performance-approach goals, emotional engagement, cognitive engagement, and performance-avoidance goals. The variance explained in the engagement components ranged from 47% to 60%. Some of the participants’ engagement and motivation in science were negatively affected by distance education. Suggestions were made to foster students’ engagement and motivation in distance science education.